Transnational Mobility and Utilization of Health Services in Northern Thailand: Implications and Challenges for Border Public Health Facilities - Natthani Meemon; Seung Chun Paek; Penchan Pradubmook Sherer; Wilasinee Keetawattananon; Thammarat Marohabutr (SAGE Publishing, 2021)
Introduction/Objective: Transnational populations from the Association of Southeast Asian Nations are crossing borders regardless of whether their status is legal or undocumented, to receive health services in the border regions of Thailand. The implications and challenges of transnational mobility and the utilization of public health facilities in Thailand's border regions are therefore investigated in this study. Methods: Four public health facilities were selected, located in 2 economically-active border areas in Northern Thailand: Mae Sai-Tachileik at the Thailand-Myanmar border and Chiang Saen-Ton Phueng at the Thailand-Lao PDR border. Qualitative data were obtained from in-depth interviews with 8 medical and non-medical hospital staff responsible for implementing facility-level policies and providing health services for the transnational population. Results: Five themes were identified through analysis of the implications and challenges for transnational mobility and the utilization of public health facilities under study: contextual determinants of illness in specific border areas; uncompensated care as opposed to financial management in serving the transnational population; health service opportunities for the transnational population; cross-border collaboration on public health; and the remaining challenges of transnational mobility in border regions. Conclusion: Conventional content analysis with interpretative induction of in-depth interview data offers recommendations for improving the capacity of border health facilities to reduce the burden placed upon them to provide services to the transnational population.